2015
DOI: 10.1007/s10967-015-4284-1
|View full text |Cite
|
Sign up to set email alerts
|

99mTc labeled plumbagin: estrogen receptor dependent examination against breast cancer cells and comparison with PLGA encapsulated form

Abstract: Plant origin products having anticancer properties come into prominence due to widespread of cancer. Plumbagin has various biological activities like anticancer activity. Estrogen receptor (ER) specificity of plumbagin (PL) and radiolabeled PL investigated by in vitro studies on ER? and ER-adenocarcinoma cells. Additionally, PLGA encapsulation was carried out to reduce toxicity of plumbagin and encapsulation effect was investigated. Plumbagin radiolabeled with 100 % in yields and had ER specificity. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Several studies found that plumbagin potently exhibited an anticancer effect against estrogen receptor (ER)-positive cell lines. Furthermore, plumbagin had a high specificity for ERs that were highly expressed in MCF-7 cells, but a low specificity for MDA-MB-231 cells [ 42 ]. Therefore, in this investigation, we aim to investigate the impact of plumbagin on the ER-positive MCF-7 cell line associated with HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that plumbagin potently exhibited an anticancer effect against estrogen receptor (ER)-positive cell lines. Furthermore, plumbagin had a high specificity for ERs that were highly expressed in MCF-7 cells, but a low specificity for MDA-MB-231 cells [ 42 ]. Therefore, in this investigation, we aim to investigate the impact of plumbagin on the ER-positive MCF-7 cell line associated with HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Plumbagin (PL) that is a plant origin product, has various biological activities like anticancer activity and specificity to estrogen receptor (ER), was used. Yurt Kilcar et al radiolabeled PL and investigated in vitro studies on ER + and ERadeno carcinoma cells [31]. Additionally, poly (D,L-lactide)-coglycolide (PLGA) encapsulation was carried out to reduce toxicity of PL and encapsulation effect was investigated.…”
Section: Wang Et Al Designed and Synthesized [ 111mentioning
confidence: 99%
“…So, the authors conclude the PL has a favorable potential on ER specific breast cancer diagnosis and PLGA encapsulation has a positive effect on this potential increasing its ER specificity. Therefore, within the naturally occurring naphthoquinones PL, as a promising anticancer agent will necessitate further deep investigation for a probable use for diagnosis of ER+ breast cancer.PL as a promising agent for the diagnosis of ER + breast cancer [31].…”
Section: Wang Et Al Designed and Synthesized [ 111mentioning
confidence: 99%